Exploration of the toponymy of Terentang Village, West Bangka as an effort to preserve culture - Figo Dwi Apriadi; Dini Harnaini; Revi Mariska; Sintia Sintia; Haura Wafa Qasthalani; Aprilia Utami; Shibyan Heryawan; Supardi Supardi; Olly Orva Peggy Kim Carla; Mawaddah Isnaini Sriwijaya; Vika Martahayu (Universitas Muhammadiyah Magelang, 2024)
The issue at hand is the low level of knowledge among the community regarding the origin of Terentang Village. The objective of this community service program is to establish toponyms and educate the community about the background of Terentang Village while uncovering its cultural potential. The activities are conducted through educational outreach methods. The outcome of this program is the exploration of toponyms that reveal the origins of several place names, such as hamlets, rivers, and hills. Through a name, the origin story of a region can be transformed into cultural heritage worth preserving. Additionally, the community's knowledge regarding the origins of their area is also enhanced.